2005
DOI: 10.1074/jbc.m501340200
|View full text |Cite
|
Sign up to set email alerts
|

Myocilin Mutations Causing Glaucoma Inhibit the Intracellular Endoproteolytic Cleavage of Myocilin between Amino Acids Arg226 and Ile227

Abstract: Myocilin is a secreted glycoprotein of unknown function that is ubiquitously expressed in many human organs, including the eye. Mutations in this protein produce glaucoma, a leading cause of blindness worldwide. To explore the biological role of myocilin and the pathogenesis of glaucoma, we have analyzed the expression of recombinant wild type and four representative pathogenic myocilin mutations (E323K, Q368X, P370L, and D380A) in transiently transfected cell lines derived from ocular and nonocular tissues. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
114
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(118 citation statements)
references
References 36 publications
4
114
0
Order By: Relevance
“…1A). Published data suggest that the C-terminal fragment of myocilin is secreted (3,23,66), while data concerning secretion of the N-terminal fragment are controversial (23,66). To test whether N-and C-terminal fragments of myocilin are (52) and anti-FLAG antibodies, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1A). Published data suggest that the C-terminal fragment of myocilin is secreted (3,23,66), while data concerning secretion of the N-terminal fragment are controversial (23,66). To test whether N-and C-terminal fragments of myocilin are (52) and anti-FLAG antibodies, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…heart and skeletal muscle) and in ocular tissues, such as iris, ciliary body (CB), and trabecular meshwork (TM) (3)(4)(5)(6)(7)(8). The protein is also present in aqueous humor (9,10). Interestingly, most MYOC mutations reported to date in sporadic cases of primary open angle glaucoma are heterozygous and are confined to exon 3 (2,5,6,(11)(12)(13).…”
mentioning
confidence: 99%
“…Interestingly, most MYOC mutations reported to date in sporadic cases of primary open angle glaucoma are heterozygous and are confined to exon 3 (2,5,6,(11)(12)(13). Recently, we showed that myocilin undergoes an intracellular endoproteolytic cleavage in the endoplasmic reticulum (ER) between amino acids Arg 226 and Ile 227 located in the putative linker domain (10). This processing predicts the production of two fragments corresponding to the N-and C-terminal domains.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence for physiological processing of other molecules that contain olfactomedin domains. For example, myocilin was recently shown to be cleaved endoproteolytically in the linker region between the N-terminal and olfactomedin domains (43). However, details concerning the processing of other olfactomedin domain-containing proteins and what differences or similarities that such processing may have to the processing of gliomedin described here remain to be characterized.…”
Section: Discussionmentioning
confidence: 89%